Multimodal Raman spectroscopy and optical coherence tomography for biomedical analysis. Issue 3 (20th November 2022) - Fitzgerald, Sean; Akhtar, Jobaida; Schartner, Erik; Ebendorff‐Heidepriem, Heike; Mahadevan‐Jansen, Anita; Li, Jiawen
Abstract: Optical techniques hold great potential to detect and monitor disease states as they are a fast, non‐invasive toolkit. Raman spectroscopy (RS) in particular is a powerful label‐free method capable of quantifying the biomolecular content of tissues. Still, spontaneous Raman scattering lacks information about tissue morphology due to its inability to rapidly assess a large field of view. Optical Coherence Tomography (OCT) is an interferometric optical method capable of fast, depth‐resolved imaging of tissue morphology, but lacks detailed molecular contrast. In many cases, pairing label‐free techniques into multimodal systems allows for a more diverse field of applications. Integrating RS and OCT into a single instrument allows for both structural imaging and biochemical interrogation of tissues and therefore offers a more comprehensive means for clinical diagnosis. This review summarizes the efforts made to date toward combining spontaneous RS‐OCT instrumentation for biomedical analysis, including insights into primary design considerations and data interpretation. Abstract : This review summarizes the efforts made to date toward combining Raman Spectroscopy (RS) and Optical Coherence Tomography (OCT) into a single instrument and aims to serve as a "one‐stop" guide for researchers interested in the field. It first outlines the essential features of RS and OCT, followed by an overview of how the two modalities can be integrated with instrumentation and how data from each is analyzed and combined. Lastly, a summary of reported biomedical applications of RS‐OCT is provided, as well as the associated challenges of multimodal RS‐OCT and future prospects.